Formation of Fiber Length in High-Generation Hybrids Obtained Through Ecological-Geographical Long-Term Hybrids - Yuldasheva R.A.; Sotvoldiyeva O.I.; Namazov Sh.E. (Web of Journals Publishing, 2023)
In this article, based on the study of the formation and stabilization of fiber length characteristics in the soil-climate field experiments of PSUEAITI of Andijan and Tashkent region of ecologically-geographically and genetically distant high-generation hybrids, the fiber length is high by involving ecologically-geographically distant forms in hybridization. It was determined that it is possible to isolate families and achieve positive results in high-generation hybrids, and the obtained results are reflected in the article.
Keywords: cotton samples, ecological-geographic distant hybrids, fiber length, variation, dispersion, genotype, hybrid, family, model variety.